ARBOREAL POETICS IN HOWARD NEMEROVS THE THOUGHT OF TREES AND LUIS H. FRANCIAS LESSONS OF A TREE - Henrikus Joko Yulianto (Sanata Dharma University, 2020)
This paper discusses arboreal poetics in two contemporary poems The Thought of Trees by Howard Nemerov, an American poet and Lessons of a Tree by Luis H. Francia, a Filipino one. The objectives of this research are first to identify how Nemerov and Francias vegetal poetics conveys ecological views; second, how their vegetal poetics evokes ones ecological awareness to conserve biodiversity and to consume material goods sufficiently. These behaviors help to reduce the exacerbation of climate change phenomenon. This research used qualitative methods, in which the data were words and taken from the two poems and from several sources on trees, climate change, ecopoetry as a kind of criticism belonging to environmental humanities. The result shows that both poems anthropomorphize trees as indispensably interconnected and coexistent with any life forms and the physical environment. This further impacts on humans growing ecological conscience not to objectify but to conserve vegetation in particular and other natural resources in general through his sufficient consumption of the material goods for ones living necessities.